PERTUMBUHAN Aquilaria spp DENGAN PEMBERIAN PUPUK KANDANG DAN MULSA DI TANAH ULTISOL PADA LAHAN TERBUKA - Idris, Muhamad; Muin, Abdurrani; Burhanuddin, . (Universitas Tanjungpura, 2017)
In the first phase of planting, Aquilaria spp. can only grow in the shade because these plants have semitoleren properties. This condition makes the Aquilaria spp difficult to grow in open fields. Thus, this research was conducted with the treatment of manure and mulch. This research aims to investigate the influence of manure and mulch on the growth of Aquilaria spp. which is planted on ultisol soil in open fields. The research was carried out in an experiment fields of Tanjungpura University in Desa Pak Laheng, Toho sub district, Mempawah region. The research was done until the plant reached the age of 3 months, using a factorial experiment with randomised block design. The treatment started from plants treated without fertilizer (P0), plants with 500-gram fertilizer (P1), and plants treated with 1000-gram fertilizer (P2), as well as with the second factor on plants without mulch (M1) and plants treated with mulch (M2). The results showed that manure gave a clear influence towards height accretion, leaf accretion, and the increase in diameter. Meanwhile, mulch only gave influences towards the increase of diameter.Â The interaction of both treatments did not give any influence on the growth of Aquilaria spp. Keywords: Aquilaria spp, manure and mulch, ultisol soil and open fields